RECRUITMENT SYSTEM FOR ELECTRONIC AND IMPROVEMENT CONTRACT - Carrasco Salazar, Charlie (2015)
This topic assumes in the first instance, a generic review of contracts by electronic means insert in a globalized society, also, the study of recent legislative innovations, according to the progress of electronic digital technologies related to contracts.